BUILDING A CULTURE OF RESILIENCE: INTEGRATING PRO- ENVIRONMENTAL BEHAVIOR INTO DISASTER RECOVERY EFFORT - Julian Amriwijaya; Sunggoro Trirahardjo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Disaster resilience depends not only on infrastructure and preparedness, but also on how pro-environmental behavior is integrated into the recovery process. This article discusses the importance of adopting environmentally friendly practices in disaster recovery efforts to create more sustainable resilience. By implementing strategies such as efficient waste management, ecosystem rehabilitation, and responsible use of natural resources, communities can reduce the environmental impacts of disasters and improve their preparedness for future risks. In addition, community participation, government policies, and cross-sectoral collaboration are key to building an environmentally oriented culture of resilience. Through education and community-based programs, awareness of the importance of pro-environmental behavior can be increased, so that disaster recovery focuses not only on physical aspects but also on ecosystem sustainability. By integrating sustainability principles into disaster recovery, communities can create systems that are more resilient and adaptive to environmental changes. This approach not only reduces the risk of future disasters but also supports sustainable development that takes into account the balance between social, economic, and ecological aspects.